Health for women. Child abuse - Memorial University of Newfoundland. Extension Service (Producer) (MUN Extension Service, 1975)
Panelists Dr. Gordon Gosse, Vivian Hoyles, and Dr. Lois Hayweiser speak about child abuse and neglect.